Gambaran Sosio Budaya Gizi Pada Balita Stunting Usia 6-24 Bulan Di Kecamatan Kalisat Kabupaten Jember - Farida Wahyu Ningtyias; Fahrun Faradila; Sulistiyani S. (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2021)
Stunted or short is a condition of failure to thrive in infants (0-11 months) and children under five (12-59 months) due to chronic malnutrition, especially in the first 1,000 days of life so that the child is too short for his age. Culture is one of the indirect factors that affect the nutritional status of children. There are several kinds of socio-culture that affect nutritional problems, namely Food Value, Food Belief, Food Idea, Food Hot-Cold, and Food Taboo. So that various socio-cultural conditions will have an influence on different parenting styles and need to get attention related to the prevalence of malnutrition that occurs. Besides that, Indonesia, which consists of many rural areas, is also an area with a high prevalence of disease in children under five or around 57.9% which can affect the nutritional status of their toddlers. The results showed that the characteristics of toddlers and families that all toddlers were aged (6-24 months) and the majority were male. The socio-cultural nutrition of mothers during pregnancy and breastfeeding shows that the majority of respondents still believe in the myths that develop in society and practice certain dietary restrictions and recommendations.